Maternal Diet-Induced Obesity Compromises Oxidative Stress Status and Angiogenesis in the Porcine Placenta by Upregulating Nox2 Expression - Cheng‐Jun Hu; Yunyu Yang; Jiaying Li; Hao Wang; Chuanhui Cheng; Linfang Yang; Qiqi Li; Jinping Deng; Zuman Liang; Yulong Yin; Zhengjun Xie; Chengquan Tan (2019)
Maternal obesity is associated with placental oxidative stress. However, the mechanism underlying this association remains poorly understood. In the present study, a gilt obesity model was developed by exposure to different energy diets and used to investigate the role of NADPH oxidase 2 (Nox2) in the placenta. Specifically, 99 gilts (Guangdong Small-ear Spotted pig) at day 60 of gestation were randomly assigned to one of the following three treatments: low-energy group (L, DE = 11.50 MJ/kg), medium-energy group (M, DE = 12.41 MJ/kg), and high-energy group (H, DE = 13.42 MJ/kg), with 11 replicate pens per treatment and 3 gilts per pen. At the start of the study, maternal body weight and backfat thickness were not significantly different in the three treatments. After the study, data indicated that the H group had higher body weight and backfat thickness gain for gilts during gestation and lower piglet birth weight compared with the other two groups. Additionally, the H group showed glucolipid metabolic disorders and increased triglyceride and nonesterified fatty acid contents in the placenta of gilts. Compared with the L group, the H group exhibited lower mitochondrial biogenesis and increased oxidative damage in the placenta. Importantly, increased mRNA expression and protein abundance of Nox2 were observed for the first time in H group placentae. Furthermore, compared with the L group, the H group showed a decrease in the density of placental vessels and the protein levels of vascular endothelial cadherin (VE-cadherin), vascular endothelial growth factor A (VEGF-A), and phosphorylation of vascular endothelial growth factor receptor 2 (p-VEGFR2) as well as the immunostaining intensity of platelet endothelial cell adhesion molecule-1 (CD31). Our findings suggest that maternal high-energy diet-induced obesity increases placental oxidative stress and decreases placental angiogenesis possibly through the upregulation of Nox2.